Politeness Strategies and Local Cultural Values in EFL Classroom Interaction: Evidence from a Vocational High School in North Buton - sufrianti purnama; Nurul Aisyah Arif; Yuliyanah Sain (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2026)
Effective classroom interaction in English language learning requires pragmatic competence, including the appropriate use of politeness strategies. However, research on EFL teachers' politeness strategies in vocational high school classrooms within local cultural contexts remains limited. This study aimed to explore the politeness strategies employed by EFL teachers and examine the influence of local cultural values on their classroom communication practices. A qualitative case study design was employed involving three English teachers at a vocational high school in Southeast Sulawesi, Indonesia. Data were collected through semi-structured interviews and classroom observations and analysed using the interactive model of Miles, Huberman, and Saldaña. Findings revealed that positive politeness strategies were most predominantly used, while negative politeness and off-record strategies served to maintain discipline and protect students' feelings. Local cultural values emphasizing respect, courtesy, and harmony also shaped teachers' communication practices. Politeness functions as both a sociocultural and pedagogical resource, indicating that teacher professional development programs should integrate politeness awareness and local cultural values.